Estudo de modelos composicionais de óleo na injeção contínua de vapor - Cavalcante, Liara Tavares (2011)
The objective of the thermal recovery is to heat the resevoir and the oil in it to increase its recovery. In the Potiguar river basin there are located several heavy oil reservoirs whose primary recovery energy provides us with a little oil flow, which makes these reservoirs great candidates for application of a method of recovery advanced of the oil, especially the thermal. The steam injection can occur on a cyclical or continuous manner. The continuous steam injection occurs through injection wells, which in its vicinity form a zone of steam that expands itself, having as a consequence the displace of the oil with viscosity and mobility improved towards the producing wells. Another possible mechanism of displacement of oil in reservoirs subjected to continuous injection of steam is the distillation of oil by steam, which at high temperatures; their lighter fractions can be vaporized by changing the composition of the oil produced, of the oil residual or to shatter in the amount of oil produced. In this context, this paper aims to study the influence of compositional models in the continuous injection of steam through in the analysis of some parameters such as flow injection steam and temperature of injection. Were made various leading comparative analysis taking the various models of fluid, varying from a good elementary, with 03 pseudocomponents to a modeling of fluids with increasing numbers of pseudocomponents. A commercial numerical simulator was used for the study from a homogeneous reservoir model with similar features to those found in northeastern Brazil. Some conclusions as the increasing of the simulation time with increasing number of pseudocomponents, the significant influence of flow injection on cumulative production of oil and little influence of the number of pseudocomponents in the flows and cumulative production of oil were found